The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1111/j.1469-0691.2006.01637.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of Mycobacterium tuberculosis

Abstract: Tuberculosis continues to be the main cause of death from a single infectious agent in developing countries. The causative agent, Mycobacterium tuberculosis, is thought to have diverged from its common ancestor as recently as 15,000 years ago. Subsequently, various genetic elements have evolved over time at different rates and can be used to elucidate patterns of infection. When individual elements are studied within genetic families, very low rates of variation are observed for almost every marker. For exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…However, there was some association of specific IS6110-RFLP patterns with disease presentation, suggesting that some strains may have the ability to disseminate more easily than others. Similarly, studies performed in Vietnam reported that the Euro-American lineage (corresponding to the modern group 2 strains [5]) associated with radiographically detected lung consolidation in pulmonary TB patients was more likely to result in pulmonary TB than meningeal TB (59) and less likely to cause extrapulmonary disease (12). In The Gambia, contacts exposed to Beijing strains were most likely to develop TB disease (14).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, there was some association of specific IS6110-RFLP patterns with disease presentation, suggesting that some strains may have the ability to disseminate more easily than others. Similarly, studies performed in Vietnam reported that the Euro-American lineage (corresponding to the modern group 2 strains [5]) associated with radiographically detected lung consolidation in pulmonary TB patients was more likely to result in pulmonary TB than meningeal TB (59) and less likely to cause extrapulmonary disease (12). In The Gambia, contacts exposed to Beijing strains were most likely to develop TB disease (14).…”
Section: Discussionmentioning
confidence: 92%
“…The strain distribution was similar to that described in a previous study (24). Then, for the analysis, we considered the phylogeny described elsewhere (5,9), where the M. tuberculosis strains were divided into an "ancient" strain group (spoligotypes of the East African-Indian [EAI] family) and a "modern" strain group, with modern group 1 including the Beijing and Central Asian (CAS) families and modern group 2 containing the T (undefined family), Haarlem, LAM, U, X, and S families (Fig. 1B).…”
Section: Methodsmentioning
confidence: 99%
“…SNPs within this gene could likely be an indication of common evolutionary ancestor with environmental isolates. Similarity, SNPs in cytochrome P450 enzymes (Table 5) that catalyze mixed oxidation of hydrophobic compounds associated with free-living saprophyte (Arnold, 2007), another indication of a common environmental ancestor for M. ap . Finally, genes encoding cytochrome P450 were shown to play a role in the persistence of M. tuberculosis in tissues (McLean et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the acquisition of drug resistance depends on the MT subgroup. Beijing type strains are relatively abundant among MDR and XDR strains (for a review of the other features of such strains, see [3]). An attempt was made to hypothesize that the fact that such strains tend to acquire MDR is associated with their higher mutability, but the frequency of spontaneous rifampi cin resistance mutations in vitro was the same as in other MT types [102].…”
Section: Tolerance and Latencymentioning
confidence: 99%
“…All of the MTC members are subspecies of one species, which is also termed MT. There are seven such subspecies (M. tuberculosis, M. africanum, M. bovis, M. caprae, M. pinnipedi, M. microti, and M. cannettii, also known as M. prototuberculosis), which have the same charac teristics of the 16S rRNA genes and differ only in structure of certain genome regions [2,3]. MT (earlier referred to as M. tuberculosis hominis) is the most sig nificant for medicine.…”
Section: Introductionmentioning
confidence: 99%